Cuddyside, Peebles, 1993-94 (Scottish Historical and Archaeological Internet Reports, 2003)
The archaeological sequence has been divided into seven separate phases of activity spanning some 600-800 years. Each phase represents a distinct change of activity on the site. The phases are as follows: phase 1 - dumping, flooding and hillwash (12th-15th century); phase 2 - medieval development; phase 3 - drainage; phase 4 - imported soils; phase 5 - late medieval development; phase 6 - 18th- and 19th-century landscaping; and phase 7 - 20th century.